On a Vehicular Suspension for a Non-ideal and Nonlinear Orchard Tower Sprayer Through an Inverted Pendulum Using Reologic Magneto (MR) - Penitente, Paulo Augusto [UNESP]; Silva, Emily Vivianne Freitas da [UNESP]; Souza, João Paulo do Vale [UNESP]; Jorge, Caroline de Freitas [UNESP]; Bittencourt, Ana Beatriz Bueno Carlini [UNESP]; Santos, Daniela Micheline dos [UNESP]; Melo Neto, Clóvis Lamartine de Moraes [UNESP]; Goiato, Marcelo Coelho [UNESP] (Springer Nature, 2022)
In this paper, analysis of the nonlinear dynamics responses of a structure equipped with a vehicle suspension that uses a fluid with magneto rheological characteristics to control the possible instability and chaotic motion. It is a spray orchards of tower type, with an unbalanced electric motor (Non-ideal) located at the top of the tower representing the concentrated mass of their fans, which represents the real system the best way possible. The simulations show that the MR suspension reduce the amplitude of oscillations of all the masses of the system, being the most important the mass of the cart and fans. The influence of the non- ideal motor is important to check the influence of a possible imbalance of fans.
Keywords: Magneto- Rheological fluid damper; Non-ideal system; Nonlinear dynamics; Spray orchards type tower; Vehicle suspension